Water resources and sustainable development: planning requirements and shared management between Spain and Portugal - López López, Alejandro (Observatorio Medioambiental, 2011)
The Earth has a constant quantity of water, but suffers hydric stress and forecast of future is not optimistic. Thus, the UN in the “Millennium Devolopment Goals for 2015” establishes special reference to the issues of water. This paper highlights the indicators of sustainability for the hydirc resources and proposes an ecosistemic model of eco-social efficiency for the sharing plannig and management between Spain and Portugal.